Menelisik Jaringan Ulama Hadis di Nusantara: Kajian atas Manuskrip Alfiyyah al-â€˜IrÄqÄ« fÄ« Muá¹£á¹alÄá¸¥ al-á¸¤adÄ«á¹¡ - Jamaluddin Jamaluddin (IAIN Syekh Nurjati Cirebon, 2023)
This article attempts to investigate the network of hadith scholars in the archipelago through the manuscript Alfiyyah al-'IrÄqÄ« fÄ« Muá¹£á¹alÄá¸¥ al-á¸¤adÄ«á¹¡ (AIMH). This book is one of the hadith science libraries written in the early period of the codification of hadith science. The book studied in this article is a manuscript that is in the Laboratory of the Faculty of Ushuluddin, Adab and Humanities UIN KH. Prof. Saifuddin Zuhri Purwokerto and no one has studied it yet. Therefore, this article attempts to reveal the manuscript of this book through historical-codicological studies. The results of this study reveal that so far the hadith science literature in the archipelago at the turn of the century XIX and XX only refers to some works of local scholars. such as Sheikh Mahfudz al-Termasi, but stillÂ little mentions the literature on hadith science composed by Middle Eastern scholars who are studied by Muslims in the archipelago, especially Java. With the discovery of this manuscript, it certainly reveals the fact that the true study of hadith in the archipelago in the early period of the XX century reached a high level, because the book Alfiyyah al-'IrÄqÄ« fÄ« Muá¹£á¹alÄá¸¥ al-á¸¤adÄ«á¹¡ fÄ« Muá¹£á¹alÄá¸¥ al-á¸¤adÄ«á¹¡ is is one of the hadi hadith science libraries after the period of codification of hadith. Therefore the contents of the book include various matters regarding the science of hadith which are collected in one book. Not only that, the Alfiyyah al-'IrÄqÄ« fÄ« Muá¹£á¹alÄá¸¥ al-á¸¤adÄ«á¹¡ manuscript also emphasizes the position of teaching hadith science in the archipelago which is connected to the transmission of hadith scholarship in the Hijaz.